Maximum utilisation of available resources for efficient poultry feeding in the South Pacific: major issues and prospects. Issue 2 (1st June 2019) - Devi, A.; Diarra, S.S.
Abstract : Feed cost is a major impediment to commercial poultry production in the South Pacific region because traditional feed ingredients (grains and oilseeds) are not grown in the region and imported at high price. As a result, meat has to be imported, which in Fiji increased by 69% between 2010 and 2011 (Diarra, 2017 ). Samoa was valued at about US 17 million or 87% of total cost of meat import in the country in 2012 and 2013. Several ingredients, which are available locally, could be included to reduce feed cost in the region. By-products of root/tuber harvest (peels and leaves), low value crops, fruits and by-products (peels and pulps), oil cakes (copra and palm kernel), by-products from the brewery, livestock/poultry slaughter, hatchery and fish processing and insect meal are readily available in most countries of the region. With adequate processing and correct diet formulation, these materials could replace reasonable proportions of the conventional energy and protein ingredients and reduce feed cost. Several factors including the type and source of material, processing method, diet composition, species, age and class of poultry affect the dietary recommendations of alternative ingredients. Currently however, the use of these resources in feed production in the region is limited due to lack of processing and analytical facilities, likely presence of antinutritional substances and poor knowledge on their nutritive value. Continued research into processing technology, regular training for farmers and extension staff and establishment of community owned feed processing units for optimum utilisation of locally available resources will benefits the poultry industry in the region.